Blind Puncture in Comparison With Fluoroscopic Guidance in Percutaneous Nephrolithotomy: a Randomized Controlled Trial - Basiri, Abbas; Mehrabi, Sadrollah; Kianian, Hamidreza; Javaherforooshzadeh, Ahmad; Kamranmanesh, Mohammad Reza (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: Our aim was to evaluate blind puncture in percutaneous nephrolithotomy (PCNL) for decreasing the risk of radiation. Materials and Methods: One hundred candidates for PCNL were randomly assigned into 2 groups. Blind access was performed for the patients in group 1 and the standard access using fluoroscopy for those in group 2. In group 1, displacement of the targeted calyx in the prone position was estimated by fluoroscopy comparing to the image on intravenous urography. Puncture of the calyx was attempted 3 cm to 4 cm below the marked site of the targeted calyx with a 30Â° angle. If the access to the collecting system was felt and urine came out, the site of puncture would be controlled by fluoroscopy. If the access failed, we would repeat puncturing up to 5 times. Results: The mean time to access was 6.6 Â± 2.1 minutes and 5.5 Â± 1.7 minutes in groups 1 and 2, respectively (P = .008). The mean time of radiation exposure was 0.95 Â± 0.44 minutes in group 2. A successful puncture to the targeted calyx was achieved in 50% and 90% of the patients in groups 1 and 2, respectively (P < .001) and a successful calculus removal in 62% and 100% of the patients in groups 1 and 2 (P < .001). Conclusion: Although about half of the patients benefited from blind access in our study, this technique can not be solely relied on, and fluoroscopy or ultrasonography should be available for prevention of complications. Â